Cherchell: An Algerian Mediterranean Historical City with a Rich Islamic Heritage Housing - BEHIRI, Abdelkader; Chabbi-Chemrouk, Naima (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2015)
Islamic residential architecture has some common architectural and architectonic elements issued from shared values such as privacy, simplicity and sobriety. Applied to residential architecture, these values led to some characteristic spaces and architectural elements such as patios or arcs. However, the Islamic civilisation is composed by different cultures spread on a great geographical area; this variety induced different interpretations of these elements by using different building shapes or materials. In this paper, we will present an example of this interpretation in the historical coastal city of Cherchell in northern Algeria. The city of Cherchell is a historic coastal city that witnessed the passage of several civilizations before the arrival of the Islamic one since its founding more than 2500 years ago. This specific situation as historical coastal city allowed the exchange with different civilizations around the Mediterranean Sea, giving rise in the Islamic period to a typical earth architecture characterised by a specific arch’s typology. The objective of this article is to present an interpretation of Islamic heritage housing architecture in a Mediterranean historical coastal city (through two specific elements: building material and architectonic element). The long term aim of this study is the dissemination of traditional technics and know-how in order restore cultural heritage buildings and construct new projects with a strong Islamic identity.